Crossbreeding in dairy cattle - Lundgren, Angelica (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2011)
The aim of this literature review is to give an overview of the differences between pure- and crossbreeding systems. Crossbreeding is a mating system with individuals of different lines or breeds. It is one of several breeding strategies in dairy production used to increase the economic profit. The use of crossbreeding increases due to changes in the dairy market and an increase of inbreeding among purebred Holstein. The main benefit of crossbreeding is heterosis, which is the improvement in genetic level in a hybrid offspring above the average of the parent breeds. Results from several studies have shown that crossbreeding is the most profitable breeding strategy, with a high level of heterosis for traits associated with fertility, health and overall fitness along with only a slightly reduced milk production. Even if more research is needed to give accurate conclusions, the most profitable breeding system, according to this review, was the three way rotational crossbreeding system.